Comparison of fiber post bond strength to root dentin using three types of resin cements - Ramin Mosharraf; Aref Sadeghian (Tehran University of Medical Sciences, 2018)
Background and Aims: In endodontically treated teeth, the fiber posts are used to retain a core restoration. The purpose of this study was to evaluate the effect of different resin cements on the bond strength of fiber reinforced composite posts to root canal dentin, and comparing the bond strength in different sections of root. Materials and Methods: In this in-vitro experimental study, 48 extracted single-canal central incisors were endodontically treated. For the push out test, the posts were divided into 3 groups according to one of the following three different cement materials (n=16) (Bifix SE, Bifix QM, Rebilda). Three slices with a thickness of 2-mm were prepared of each root. The push-out tests were performed at a cross-head speed of 1 mm/minute using a universal testing machine. Data were analyzed by two-way and one-way ANOVA test followed by Tukey post hoc test (α=0.05). Results: There was no significant differences between the mean push out bond strength of three experimental groups (P=0.650), but there were significant differences between the mean push out bond strength of root dentin regions (P<0.001). Conclusion: Under the conditions of this study, there was no significant difference between the mean push out bond strength of 3 different resin cement systems. The coronal region of root dentin showed significantly higher mean bond strength values than that of the middle and apical thirds.